Technical, Financial and Social Cultural of Feasibility Analysis of Combine Harvester in Rice Agribusiness in Tulang Bawang District, Lampung Province - Hendra Saputra (Journal of Global Sustainable Agriculture, 2021)
The objectives of this research were (1) to study the technical aspect of the combined harvester, (2) to calculate the feasibility of rice agribusiness using a combined harvester, (3) to measure adoption level of farmers towards combine harvester in Tulang Bawang District, Lampung Province. The research was carried out in two subdistricts, namely Rawajitu Selatan (represented by Gedung Karya Jitu village) and Rawapitu (represented by Bumi Sari village) of Tulang Bawang district from August 2015 to December 2015, and used survey method. The studied sample of 60 farmers (or 14.90% of 972) was determined with proportional random sampling.  Two sorts of data were collected, namely interview and direct observation on-site, and feasibility analysis on a combined harvester, including technical, financial, and socio-cultural aspects. The result revealed that from technical aspects, combine harvester needed 5 to 7 hours to harvest, produced an excellent quality of unhauled rice with affordable production cost, compared with the traditional method. The use of a combined harvester was financially feasible. This was shown by farmer income and B/C ratio, from socio-cultural aspects, farmers showed high scores of adaption level towards combine harvester, namely 16.29 and 13.06 for Gedung Karya Jitu and Bumi Sari village, respectively.